Integrating Virtual Reality into Language Acquisition: Creating Immersive and Contextual Learning Experiences for Language Learners - Roni Subhan; Ana Pereira; Elena Galli (Yayasan Adra Karima Hubbi, 2026)
Background. The integration of Virtual Reality (VR) into language education has gained significant attention in recent years due to its potential to create immersive, interactive, and contextual learning experiences. VR enables language learners to engage in real-life scenarios, fostering deeper understanding and enhancing language acquisition. Despite its growing use, there is limited research on the effectiveness of VR in providing contextualized language learning experiences that mimic real-world interactions. Purpose. This study aims to explore the effectiveness of integrating VR into language acquisition, focusing on how VR-based environments can create immersive, context-driven learning experiences that improve language proficiency. The research seeks to evaluate how these immersive experiences impact language learning outcomes in terms of vocabulary acquisition, speaking skills, and cultural understanding. Method. A mixed-methods approach was adopted, involving both qualitative and quantitative data collection. The study included a sample of language learners who participated in VR-based language learning modules. Pre- and post-tests were administered to measure language proficiency improvements, while surveys and interviews were used to gather qualitative insights into learners' experiences. Results. The findings indicate that VR-based language learning significantly improved vocabulary retention, speaking skills, and cultural understanding. Participants reported higher levels of engagement and motivation, with many highlighting the contextualized nature of the learning environment as a key factor in their success. Conclusion. Integrating VR into language acquisition offers significant potential to enhance the learning experience by providing immersive, contextualized, and engaging environments that improve language proficiency.